PENGARUH PROFITABILITAS, LIKUIDITAS, UKURAN PERUSAHAAN DAN PERTUMBUHAN PERUSAHAAN TERHADAP OPINI AUDIT GOING CONCERN (STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN (2014-2017) - Bayu Nurcahyo Andini; Soebandi Soebandi; Yantik Peristiwaningsih (Media Mahardhika, 2021)
Purpose - The purpose of this research was to determine the effect of profitability, liquidity, company size and company growth on Going Concern Audit Opinions. Research on going concern audit opinion on companies listed on the Indonesia Stock Exchange has been widely conducted, but there are still many differences in research results such as research from Setiawan and Suryono (2015) which proves that liquidity can have an influence on going concern audit opinion, in contrast to Melania research et all (2016) prove that liquidity has no significant effect on going concern audit opinion. Design / Methodology / Approach - This type of research uses Quantitative, the sample in this study uses objects in Manufacturing Companies Listed on the Indonesia Stock Exchange in 2014-2017 with a company sample of 126 and an observation period of 4 years so that the total number of samples in this study as many as 504. Findings - The results show that profitability influences going concern audit opinion, liquidity affects going concern audit opinion, company size influences going concern audit opinion, company growth does not affect going concern audit opinion and Simultaneously profitability, liquidity, company size and growth the company influences the going concern audit opinion. Research Limits - The scope covers information about profitability, liquidity, company size, company growth, and going concern audit opinion. And use manufacturing companies listed on the Indonesia Stock Exchange in 2014-2017. Implications - Investors and prospective investors in investing should pay attention to the company's financial condition, especially related to business continuity in order to make the right investment decisions. Originality / Value - Research on going concern audit opinion on companies listed on the Indonesia Stock Exchange has been widely conducted, but there are still many differences in research results. Diverse research results may be due to differences in the nature of the independent variables and the dependent variable under study or differences in the observation period